Testing The Effect of Temperature, Storage Time, The Residual Test of Neem Oil Formulation (Azadirachta indica A. JUSS) and Bitung Formulation (Baringtonia asiatica) to Its Toxicity Against Large Cabbage Heart Caterpillar (Crocidolomia pavonana F) - Widayani, Neneng Sri; Haq, Afifah Nashirotul; Dono, Danar (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
This study aims to determine the effect of temperature and storage time of neem formulation and residual test of neem formulation and bitung formulation to its toxicity on C. pavonana larvae. The formulations tested on the storability and temperature test using the newly prepared, neem formula has been stored for 19 months at room temperature 24.6-31,7 C, and stored in low temperature (4oC) as well as controls. The toxicity of the neem oil formulation was tested at concentrations of 1%, 2%, and 3%. Residual testing was performed by spraying and the residual test samples were taken on days 0,1,2,3,5,7,9,11, and 13 days after application of insecticide spraying. The results showed that storage at low temperatures (temperature 4oC) for 19 months can maintain the toxicity of the neem formulation to C. pavonana larvae. while storage at room temperature for 19 months resulted in a decreased toxicity. The residual activity of the neem formulations of concentration 0.8% and 2.4% ceased to cause the death C. pavonana larvae at the residual age of 13.34 days and 14.66 days. The activity of Bitung formulation concentration of 1.1% and 2.8% ceased to causing death C. pavonana larvae at the residual age of 11.33 days and 16.26 days.Keyword: Azadirachta indica, Baringtonia asiatica, Crocidolomia pavonana, Residue test, Storability test, Temperatures, Toxicity,